Survey of Ankle Coordination and Driving Ability of Students of SMK Negeri 4 Makassar - Achmad Karim; Muhammad Hasbillah; Herman Herman; Ikadarny Ikadarny (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
This research is a type of descriptive research that uses a "Survey" research design. This study aims to determine; To see and know the description of the level of eye-foot coordination and the ability to dribble in football games for students of SMK Negeri 4 Makassar. The population is all students of SMK Negeri 4 Makassar. The sample used was 20 people. The sampling technique is Simple Random Sampling. The data analysis technique used is descriptive analysis. The research results show that; 1) ankle coordination in students of SMK Negeri 4 Makassar is in the moderate category with a percentage of 40.00%. 2) The ability to dribble a football game for students at SMK Negeri 4 Makassar is in the moderate category with a percentage of 40.00%.